Developmental Programming: Does Prenatal Steroid Excess Disrupt the Ovarian VEGF System in Sheep?1 - Ortega, Hugo Hector (2015)
Prenatal testosterone (T), but not dihydrotestosterone (DHT), excess disrupts ovarian cyclicity and increases follicular recruitment and persistence. We hypothesized that the disruption in the vascular endothelial growth factor (VEGF) system contributes to the enhancement of follicular recruitment and persistence in prenatal T-treated sheep. Impact of T / DHT treatments from days 30-90 of gestation on VEGFA, VEGFB, and their receptor (VEGFR-1 (FLT1), VEGFR-2 (KDR), and VEGFR-3 (FLT4)) protein expression was examined by immunohistochemistry on fetal day 90, 140, 22 weeks, 10 months (postpubertal), and 21 months (adult) of age. Arterial morphometry was performed in fetal day 140 and postpubertal ovaries. VEGFA and VEGFB expression were found in granulosa cells at all stages of follicular development with increased expression in antral follicles. VEGFA was present in theca interna, while VEGFB was present in theca interna / externa, and stromal cells. All 3 receptors were expressed in the granulosa, theca, and stromal cells during all stages of follicular development. VEGFR-3 increased with follicular differentiation with the highest level seen in the granulosa cells of antral follicles. None of the members of the VEGF family or their receptor expression were altered by age, or prenatal T / DHT treatments. At fetal day 140, area, wall thickness, and wall area of arteries from the ovarian hilum were larger in prenatal T- and DHT-treated females, suggestive of early androgenic programming of arterial differentiation. This may facilitate increased delivery of endocrine factors and thus indirectly contribute to the development of multifollicular phenotype.